Specific Features of Mergers and Acquisitions in the Transport Industry - Prudius, Y.; Zaitseva, I.; Karlova, O. (International Journal of Engineering and Technology, 2018)
The article defines the role of the transport system in formation of the industrial infrastructure of the world economy in order to determine the trends to increase the efficiency of transport infrastructure in the conditions of globalization of the world economy. The authors have considered M&A processes as the most efficient means to improve the efficiency of operation of transport companies. The main reasons have been identified which motivate owners of transport companies to such types of reorganization as mergers or acquisitions. Both external and internal factors influencing the value of transport companies in mergers and acquisitions have been systematized. it was proved that one of the most priority options for the sustainable development of both an individual enterprise and the domestic economy is transnational integration transformation into forms of mergers and acquisitions. According to this scenario, the expected result is not only an increase in the company’s value, but also an increase in profits. Â Â